Protectionism and industrialization: a critical assessment of the Latin American industrialization period - Levy-Orlik,Noemi (2009)
Protectionist policies were considered one of the pivotal features of the import industrialization process in Latin America. In this paper the effects of protectionist policies are assessed in terms of the principal macroeconomic variables, productive structure and external trade composition; also, ECLAC's perspective on the import substitution process is discussed. The main conclusions are that regional protectionist policies were spontaneous, and their effects were limited due to the generalized protection that took place and the government's commitment to price stability.